Ethics of Submitting Targhib wa Tarhib Hadith on Social Media: Qawa'id al Tahdith Perspective - Ali Yusuf Muzaki; Muh.Fatihuddin; Achmad Alfan Rosyidi Khalil; Khamim Khamim (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the phenomenon of targhib wa tarhib hadith dissemination on social media through the analytical framework of the classical theory of Qawa’id al-Tahdith (principles of hadith transmission). The rise of digital technology has transformed the circulation of hadith in modern society, where many narrations are spread without proper verification of their chains of transmission or contextual understanding. Such practices have raised critical issues concerning authenticity, interpretation, and ethical communication in Islamic preaching. This research applies a qualitative method with a library-based approach, supported by phenomenological analysis of digital da'wah content across several social media platforms. The findings reveal that most targhib wa tarhib hadiths circulating online lack clear sources and authenticity status, leading to potential misinterpretations of Islamic teachings. The principles of Qawa’id al-Tahdith such as caution (taharri), selectivity (tamyiz), and awareness of the audience’s condition (ma’rifat hal al-mukhatab) are highly relevant as ethical guidelines for hadith dissemination in the digital era.